KARAKTERISTIK KOMUNIKATOR YANG EFEKTIF DALAM KOMUNIKASI ANTAR PRIBADI - Fifi Hasmawati (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2020)
The character of communicator is called by Aristotle as ethos. Ethos consists of good thoughts, good morals, and good intentions. Another term for ethos is credibility, which consists of two elements, namely expertise and trustworthiness. Another element is the attraction of the communicator and power. This paper contains the characteristics of communicators in interpersonal communication. The three characters mentioned above are the basic characters that must be fulfilled by communicators. However, this character still needs to be complemented by the importance of a Communication Control Pattern so that Interpersonal Communication can be effective.